2015
DOI: 10.1002/jsfa.7273
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on pasture versus indoor feeding of dairy cows

Abstract: The dairy industry in many regions of the world has moved towards a high-input/high-output system maximising annual milk production per cow, primarily through increasing concentrate-based total mixed rations fed indoors year round, as opposed to allowing cows to feed on pasture. Pasture-based dairy systems in regions like New Zealand and Ireland are oriented towards maximum milk yield per unit of pasture, which has led to Holstein strains that are 50 to 100 kg lighter, exhibit a higher body condition score, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…Overall, concentrate levels, the degree of mechanisation (data not shown) and the lack of pasture as well as pure forage diets confirmed that project farms rank at the current upper end of the structural change of Alpine dairy farming. Larger, non-seasonal, indoor-feeding and more specialised dairy production more and more replaced the traditional, forage-based and smallscaled one in the last 50 years (Knaus 2009(Knaus , 2016.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, concentrate levels, the degree of mechanisation (data not shown) and the lack of pasture as well as pure forage diets confirmed that project farms rank at the current upper end of the structural change of Alpine dairy farming. Larger, non-seasonal, indoor-feeding and more specialised dairy production more and more replaced the traditional, forage-based and smallscaled one in the last 50 years (Knaus 2009(Knaus , 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, FV and BS had more similarities to HF compared to their breed averages. This pictured the above-average production level of the project farms and the change in Austrian dairy production towards a more specialised and intensive one (Knaus 2009(Knaus , 2016.…”
Section: Effect Of Genotypementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, from an animal welfare perspective, the negative effects of the driving down transhumance might be amplified by the recent evolution of the dairy sector in the mountains. In many alpine regions, autochthonous cattle breeds, well adapted to the alpine environment, have been indeed massively replaced by specialised dairy breeds that have more difficulty to cope with pasture grazing (Battaglini et al 2014;Knaus 2015;Stergiadis et al 2015). According to D'Hour et al (1994), the extreme walking exercise of the transhumance could be particularly detrimental for high producing dairy cattle when managed under extensive systems.…”
Section: Introductionmentioning
confidence: 99%